Pembuatan Profil Multimedia Green House Book’s And Coffe Break - Ardianto, Catur; Purnama, Bambang Eka (Speed - Sentra Penelitian Engineering dan Edukasi, 2009)
Corporate world will not get out of the publication, because publication represent the very determining factor in progress of an effort. Like green house book's and coffe break, beside satisfying service, publication represent the very important factor in determining progress from this effort During the time green house book's and coffe break have conducted he publication process pass the radio advertisement, but the mentioned not yet change to this effort. Because society or consumer not yet seen and recognize fully from this place. For that hence will be done by making of profile multimedia green house book's and coffe break able to be used as by alternative of publication media is effort this. Benefit from this research is to develop knowledge and experience specially specially in the field of technology and entertainment amusement Research methodologies the used is Bibliography, Observation, Interview, Analysis, Making Of Script and Storyboard, Intake of Picture and of Capturing, Editing and Recording Of Voice, trainning, Implementation. In this research also will be elaborated to regarding production pre phase, phase produce and phase of after production, So with the research is expected video that can be used for promotion Green House Book’s and Coffe Break.